Sociodemographic factors of families in the Patriotas neighborhood of Tunja - Peñuela Rodríguez, Fredy Enrique; Córdoba Torres, Diego Fernando (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2020)
The present study was the first approach by Family Medicine at the community level in the city of Tunja, exploring non-classical settings to provide health care. It is a descriptive study where the data was collected through a family file designed to collect information in the Project Promotion and maintenance of the health of the individual, family and community of the Los Patriotas neighborhood of the municipality of Tunja: 2019-2020 by the group of family doctors in training from the first cohort of the Family Medicine Specialization of the UPTC. 45 families were characterized and analyzed, with 151 members, finding that the households are multidimensional, with a population of children under 15 years of age (25.4% ), adolescents and adults, aged between 15 and 59 years, comprise 71.2% of the population, and 3.4% are adults over 65 years of age. Indicating that 28% of the individuals in the families are probably dependent on some other member. It was possible to determine that a large part of the population is in a productive stage and corresponds to nuclear families, but it was evidenced that the head of the household in single-parent families corresponds to 100% of the cases, presence of economic dependence, illiteracy and predominant occupation in jobs informal or low paid. We found that almost the entire population is affiliated with the health system, however, health barriers related to situations related to the use of services could be detected. Although some variables such as family dynamics and handling of rules and limits at home were not objectively estimated, some situations such as the stay at home of minors in the care of other minors and / or elderly adults were observed. The lack of recreational spaces and nearby green areas was observed, as well as the presence of outlets for psychoactive substances in the neighborhood, which deserve a more in-depth study in the future in order to propose contextualized solutions to the realities of this sector in the city of Tunja. In the context shown during the development of the research, multiple intervention opportunities were found at the individual, family and community levels by the Family Doctor, which allowed the development of health actions contextualized to the vulnerable environment in the urban area and that achieved an approach of Primary Health Care to the different scenarios of development of the population as proposed by the Comprehensive Health Care Policy (PAIS).